AN ANALYSIS ON STUDENTS’ TRANSLATION PROCEDURE OF IDIOM IN NARRATIVE TEXT - Chandra, Kusuma; Suhartono, Luwandi; Rosnija, Eni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2016)
Abstract: The purpose of this research is to find out the translation procedure used by the Semester-6 students of English Language Education Study Program at Teacher Training and Education Faculty, Tanjungpura University in Academic Year 2014/2015 in translating idiom in form of narrative text. The research method used in this reseach was descriptive study. The descriptive study was used to describe and find out the translation procedure used by Semester-6 students in their translation. The sample of this research was 24 students. The result of this study showed that there were eight procedures that students used in their translations and there are three procedures that students tend to use. They are equivalence procedure that was used 57 times (26.39%), paraphrase procedure that was used 43 times (19.91%), and literal translation procedure that was used 35 times (16.20%). Keywords: Translation, Translation Procedure, Idioms, Narrative Abstrak: Tujuan dari penelitian ini adalah untuk menemukan prosedur penerjemahan yang digunakan oleh mahasiswa semester enam Program Studi Pendidikan Bahasa Inggris Fakultas Keguruan dan Ilmu Pendidikan Universitas Tanjungpura Tahun Ajaran 2014/2015 dalam menerjemahkan idiom dalam bentuk teks narasi. Metode penelitian yang digunakan dalam penelitian ini adalah penelitian deskriptif. Penelitian deskriptif digunakan untuk menguraikan dan menemukan prosedur penerjemahan yang digunakan oleh mahasiswa semester enam dalam terjemahan mereka. Jumlah sampel pada penelitian ini adalah 24 mahasiswa. Hasil dari penelitian ini menunjukkan bahwa terdapat delapan prosedur yang digunakan oleh mahasiswa dalam terjemahan mereka dan terdapat tiga prosedur yang cenderung lebih sering digunakan. Prosedur-prosedur tersebut adalah prosedure ekuivalen yang digunakan sebanyak 57 kali (26.39%), prosedur parafrase yang digunakan sebanyak 43 kali (19.91%), dan prosedur penerjemahan literal yang digunakan sebanyak 35 kali (16.20%). Kata Kunci: Terjemahan, Prosedur Terjemahan, Idiom, Naratif